THE BACTERIAL FLORA, TRIMETHYLAMINE AND TOTAL VOLATILE NITROGEN OF FISH MUSCLE AT 3Â°C - Velankar, N K (Indian Journal of Fisheries, 2015)
Storage in ice is widely employed as a means of preservation for short durations prior to marketing of fish in the fresh condition. The use of special ices treated with antibiotics for enhancing the period of preservation is under experimentation in different countries. In this connection it is necessary to have some knowledge of the bacteria which are associated with fish at the temperatures obtaining during the storage. Further, bacteriological oteervations might be Useful in ascertaining the freshness of fish in storage. Various tests, including the determination of trimethylamine, which are in use at present, are not thoroughly satisfactory since opinions differ as to how far they are reliable as criteria of freshness (Tarr et al, 1939; Shewan, 1949).